Claudins: Beyond Tight Junctions in Human IBD and Murine Models - Čužić, Snježana; Antolić, Maja; Ognjenović, Anja; Stupin-Polančec, Darija; Petrinić Grba, Adriana; Hrvačić, Boška; Dominis Kramarić, Miroslava; Musladin, Sanja; Požgaj, Lidija; Zlatar, Ivo; Polančec, Denis; Aralica, Gorana; et al. (Frontiers in Pharmacology, 2021)
Claudins are transmembrane proteins constituting one of three tight junction protein families. In patients with inflammatory bowel disease (IBD), disease activity dependent changes in expression of certain claudins have been noted, thus making certain claudin family members potential therapy targets. A study was undertaken with the aim of exploring expression of claudins in human disease and two different animal models of IBD; dextrane sulfate sodium (DSS) induced colitis, and adoptive transfer model of colitis. The expression of sealing claudins 1, 3, 4 and 8, and pore-forming claudin 2 in humans and rodents has been evaluated by immunohistochemistry, quantitative polymerase chain reaction and western blot analysis. Claudins were expressed by epithelial and mesenchymal cells and were found to be situated at the membrane, within the cytoplasm or within the nuclei. Claudin expression by human mononuclear cells isolated from lamina propria has been confirmed by western blot. The claudin expression pattern in uninflamed and inflamed colon varied between species and murine strains. In IBD and both animal models, diverse alterations in claudin expression by epithelial and inflammatory cells were recorded. Tissue mRNA levels for each studied claudin reflected changes within cell lineage and, at the same time, mirrored the ratio between various cell-types. Based on the results of the study it can be concluded that; 1) claudins are not expressed exclusively by epithelial cells, but by certain types of mesenchymal cells as well; 2) changes in the claudin mRNA level should be interpreted in the context of overall tissue alterations; 3) both IBD animal models that were analyzed, can be used for investigating claudins as a therapy-target, respecting their similarities and differences highlighted in this study.